Assessing The Relationship Between Digital Competencies and Technostress in Higher Education - Vásquez-Pajuelo, Lida; Rodriguez-Barboza, Jhonny Richard; Bartra-Rivero, Karina Raquel; Andrade-Díaz, Elba María; Tuesta-Vila, Jazmín Alicia; Obando-Peralta, Ena Cecilia; Alarcón-Villalobos, Yvonne Jacqueline (Journal of Ecohumanism, 2024)
This study explored the relationship between digital competencies and technostress among university instructors teaching remotely in Peru. It aimed to determine whether enhancing digital skills could alleviate technostress. The research utilized a quantitative, non-experimental approach and collected data from 120 instructors from a private university in Lima, Perú using established surveys like the DigCompEdu Check-In and RED TIC. The analysis, performed through logistic regression in SPSS v27, revealed that 55.6% of instructors displayed a high level of commitment to their profession, while 58.9% exhibited adept digital pedagogical abilities. Further inferential analysis found a substantial link between digital competencies and technostress, evidenced by a Nagelkerke index of 0.622. This indicates that approximately 62.2% of the variance in technostress levels could be attributed to differences in digital skills. The findings underscore the importance of improving digital competencies among educators to significantly lower their technostress, suggesting that a greater integration of these skills in teaching practices could enhance the educational experience in digital environments.